2021
DOI: 10.3389/fvets.2021.759418
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fiber-1-Edited and Highly Attenuated Recombinant Serotype 4 Fowl Adenovirus Confers Efficient Protection Against Lethal Challenge

Abstract: Currently, a fatal disease of hepatitis-hydropericardium syndrome (HHS) caused by serotype 4 fowl adenovirus (FAdV-4) has spread worldwide and resulted in tremendous economic losses to the poultry industry. Various vaccines against FAdV-4 were developed to control the disease; however, few live-attenuated vaccines were available. In this study, we targeted the N-terminal of fiber-1 and rescued a recombinant virus FAdV4-RFP_F1 expressing the fusion protein of RFP and Fiber-1 based on the CRISPR/Cas9 technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Fiber proteins in FAdV-4 are major regulators for pathogenicity during infection, and recombinant vaccines have been developed using fiber1 and fiber2 proteins. A recombinant virus with an edited N-terminus region of the fiber1 protein protected chickens from a virulent FAdV-4 infection [ 45 ]. The fiber2 construct from a novel FAdV-4 strain was used as a vaccine and showed high protection efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Fiber proteins in FAdV-4 are major regulators for pathogenicity during infection, and recombinant vaccines have been developed using fiber1 and fiber2 proteins. A recombinant virus with an edited N-terminus region of the fiber1 protein protected chickens from a virulent FAdV-4 infection [ 45 ]. The fiber2 construct from a novel FAdV-4 strain was used as a vaccine and showed high protection efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…NHEJ and HDR pathways were applied to virus attenuation, e.g., Fan et al [10] prepared the M3 strain using Cas9 protein triple knockout HSV-1. FAdV4-egfp-rF2 and FAdV4-RFP_F1 attenuated vaccines were respectively produced by HDR recombination at different genetic loci of Fowl adenovirus 4 [11][12].…”
Section: Vaccine Preparationmentioning
confidence: 99%
“…Not only was the hexon-edited virus significantly attenuated, but the fiber-1 and fiber-2 edited viruses were rescued and identified as non-pathogenic to SPF chickens. Mu et al rescued the recombinant virus FAdV4-RFP_F1 via the CRISPR/Cas9 technique, which contained a fusion protein of RFP and fiber-1 ( 31 ). The recombinant virus was efficiently attenuated and provided full protection against the lethal challenge of FAdV-4, demonstrating that fiber-1-edited FAdV4-RFP_F1 could be a live-attenuated vaccine candidate and fiber-1 could be a potential insertion site for novel vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al firstly developed a novel genotype, FAdV-4, and identified the natural large genomic 1966bp deletion as a foreign gene insertion site ( 49 ). Mu et al also optimized the CRISPR/Cas9 operating platform to insert a foreign gene into the fiber gene of FAdV-4 ( 31 ). Meanwhile, Yan et al established an easy-to-use reverse genetics system based on Gibson assembly to modify the right and partial left genes ( 50 ).…”
Section: Introductionmentioning
confidence: 99%